The Effectiveness of One Malungon Radio-Television/Radio-Based Instruction in the Lens of Learners in the Remote Areas of East-Malungon District: A Case Analysis - Tabasondra, Ezra Lou (JPAIR Institutional Research, 2023)
This study seeks to determine the effectiveness of implementing OMR-Tele/RBI in the remote areas of the Municipality of Malungon. The research employed a qualitative case study method that utilized key informant interviews with the Junior High School learners and Focus Group Discussions (FGD) with home learning partners in Malungon, Sarangani Province. According to the findings, OMR-Tele/RBI benefits some learners, particularly junior high school learners, because they can study anywhere, anytime, and at their discretion. However, due to their short concentration span and inability to study independently, primary learners are unsuitable for OMR-Tele/RBI. Problems with OMR-Tele/RBI have also hindered remote learning. Most learners living in mountain areas have slow or even no access to radio or the internet. Moreover, the majority of learners lived in small houses with no subdivisions. Therefore, students were unable to find a peaceful place to study. As a consequence, students cannot concentrate while listening to or viewing the lessons. In addition, it was recommended that the teacher models and facilitators be equipped to construct age- and level-appropriate audio or video lessons. Additionally, the audio and video lessons should be quality-assured to ensure the program’s effectiveness.